Multicentre, randomised controlled trial of a low-cost smoking cessation text message intervention for pregnant smokers (MiQuit) - Naughton, Felix; Foster, Katharine; Emery, Jo; Cooper, Sue; Sutton, Stephen; Leonardi-Bee, Jo; Jones, Matthew; Ussher, Michael; Whitemore, Rachel; Leighton, Matthew; Montgomery, Alan; Parrott, Steve; et al. (2016)
Background: Text message cessation programmes have potential to change smoking behaviour during pregnancy but their effectiveness is unknown. This study aimed to estimate key parameters, including effectiveness and cost-effectiveness, for delivering a definitive effectiveness trial of a pregnancy specific, theory-guided, tailored text message cessation intervention.